The French art novel 1900-1930 - Shingler, Katherine (Research monographs in French studies, 2016)
The French art novel, with its tales of artists, models and creative struggles, is often thought to be a specifically nineteenth-century phenomenon, which dies out by 1900. This wide-ranging, interdisciplinary study argues that the art novel does not in fact disappear but rather undergoes a series of transformations in the early twentieth century, in step with radical changes in the visual arts of the period. Examining both well-known and all-but-forgotten novels, Shingler examines the ways in which they move on from their nineteenth-century predecessors, as the development of avant-garde movements makes questions of aesthetic value and authenticity ever more pressing; as changing gender roles increasingly put pressure on writers to acknowledge female creativity; and as the emergent art of the cinema comes to compete with painting as the primary visual reference point for writers.